The structure (Alysa) in the Holy Quran: Grammatical and Semantic study - Widda , Murtada (Al-Adab Journal, 2025)
This study aims to determine the structure (Alysa) in terms of grammatical rhetorical purpose in the Holy Quran, the study followed the descriptive analytical approaches, and thy were dealt with through two sections: Firstly, with the definition of the structure (Alysa), where the Hamza it’s interrogative purpose, and its effect on the sentence structure were addressed. And not in terms of its origin, meaning, uses, prioritization of its predicate. Inserting the (Baa) into its predicate. Secondly dealt with the structure (Alysa) in the Holy Quran from Grammatical and Semantic perspective.   The study reached many findings: the most important are; The construction of (Alysa) occurred thirteen times in the Holy Quran, eight times its predicate come in the genitive case verbally with  an extra  (Baa), and five times it predicate come before it’s noun, and  come as a semi genitive and  sentence its noun is an indefinite noun or an add indefinite noun .The parsing of the sentence (Alysa) is a number of cases which is resumption that has no place of parsing in the accusative  position of direct object of the predicate- an answer to the vocative which has no place of parsing The (Baa) a predicate has been added not for purpose of strengthening the affirmation and rebutting the negation of predicate, while the purpose of question for the structure are: report, report by exclamation, denial, rebuke, or warning and indefiniteness alone.